Uji Efektivitas Sediaan Gel Ekstrak Daun Pegagan (Centella Asiatica) terhadap Penyembuhan Luka Bakar pada Tikus Jantan (Rattus Norvegicus) - Caniago, Indri M. Clearesta; Muhammad Yunus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Burn wounds are tissue injuries caused by exposure to heat, chemicals, electricity, or radiation, which may result in both local and systemic damage. This study aims to evaluate the effectiveness of a gel formulation containing Centella asiatica leaf extract on the healing of second-degree burn wounds in male rats (Rattus norvegicus). Controlled burn injuries were induced on the rats’ backs and treated with the Centella asiatica gel at specific concentrations for 14 days. Observed parameters included wound size reduction, healing duration, and histopathological changes in the skin tissue. The results demonstrated that the Centella asiatica gel significantly accelerated the wound healing process compared to the control group. The active compounds, such as asiaticoside and triterpenoids, are believed to enhance collagen synthesis and tissue regeneration. Therefore, Centella asiatica gel has the potential to be developed as a natural therapeutic agent for burn wound healing.